Myeloid‐Related Proteins 8 and 14 Contribute to Monosodium Urate Monohydrate Crystal–Induced Inflammation in Gout. Issue 5 (May 2014) - Holzinger, Dirk; Nippe, Nadine; Vogl, Thomas; Marketon, Kristina; Mysore, Vijayashree; Weinhage, Toni; Dalbeth, Nicola; Pool, Bregina; Merriman, Tony; Baeten, Dominique; Ives, Annette; Busso, Nathalie; et al.
<x xml:space="preserve">Abstract</x> Objective Monosodium urate monohydrate (MSU) crystal–induced interleukin‐1β (IL‐1β) secretion is a critical factor in the pathogenesis of gout. However, without costimulation by a proIL‐1β–inducing factor, MSU crystals alone are insufficient to induce IL‐1β secretion. The responsible costimulatory factors that act as a priming endogenous signal in vivo are not yet known. We undertook this study to analyze the costimulatory properties of myeloid‐related protein 8 (MRP‐8) and MRP‐14 (endogenous Toll‐like receptor 4 [TLR‐4] agonists) in MSU crystal–induced IL‐1β secretion and their relevance in gout. Methods MRP‐8/MRP‐14 was measured in paired serum and synovial fluid samples by enzyme‐linked immunosorbent assay (ELISA) and localized in synovial tissue from gout patients by immunohistochemistry. Serum levels were correlated with disease activity, and MSU crystal–induced release of MRPs from human phagocytes was measured. Costimulatory effects of MRP‐8 and MRP‐14 on MSU crystal–induced IL‐1β secretion from phagocytes were analyzed in vitro by ELISA, Western blotting, and polymerase chain reaction. The impact of MRP was tested in vivo in a murine MSU crystal–induced peritonitis model. Results MRP‐8/MRP‐14 levels were elevated in the synovium, tophi, and serum of patients with gout and correlated with disease activity. MRP‐8/MRP‐14 was released by MSU crystal–activated phagocytes and increased MSU crystal–induced IL‐1β secretion in a TLR‐4–dependent manner. Targeted deletion of MRP‐14 in mice led to a moderately reduced response of MSU crystal–induced inflammation in vivo. Conclusion MRP‐8 and MRP‐14, which are highly expressed in gout, are enhancers of MSU crystal–induced IL‐1β secretion in vitro and in vivo. These endogenous TLR‐4 ligands released by activated phagocytes contribute to the maintenance of inflammation in gout.